TINJAUAN KONSTITUSIONAL TERHADAP PENYELENGGARAAN PILKADA DALAM NEGARA DEMOKRASI INDONESIA BERDASARKAN UNDANG-UNDANG NO. 8 TAHUN 2015 TENTANG PEMILIHAN GUBERNUR BUPATI DAN WALIKOTA - Dian Eka Prastiwi (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2016)
Constitution or the basic state is basically a framework for organized political society and by the law establishes arrangements regarding permanent institutions, the function of scientific equipment are certain rights that have been set. And, as a set of organizing principles of power broadly. That power is reflected in the conduct of democratic elections were held in both central and regional levels. This research was conducted with qualitative research based on secondary data. This study shows constitutional review of the implementation of the elections in Indonesia are in accordance with the law No. 8 in 2015 about the election, strengths and weaknesses in the implementation of the election has not been done efficiently but are carried out in a democratic and constitutional.Keywords: Constitution, The elections, Democration